Role of interfacial damage modeling in finite element analysis of intermediate crack debonding failure of FRP-plated reinforced concrete beams: A numerical investigation. Issue 4 (April 2016) - Chen, Guangming; Zhang, Rong; Li, Shiwei; Li, Xiaoqin
This study presents a numerical investigation into the effects of interfacial damage on the bond behaviors of the interfaces between two adjacent cracks in a fiber-reinforced polymer-plated reinforced concrete beam. The interfaces investigated herein refer to both fiber-reinforced polymer-to-concrete interface and steel-to-concrete bonded interface which were well represented in this study by a simplifying fiber-reinforced polymer-to-concrete bonded joint or steel bar-to-concrete bonded jointed joint loaded at their two ends, aiming to simulating the interaction between two adjacent flexural cracks in the fiber-reinforced polymer-plated reinforced concrete beams. Parametric studies were carried out using nonlinear finite element model built in ABAQUS to investigate the effects of a number of significant factors such as bond length, ratio of loads applied at the two ends (i.e. load ratio), and types of bond–slip models, with the main objective being to clarify the effect of interfacial damage (i.e. bondline damage) during slip reversals on the bond behaviors of the interfaces. The numerical results show that in finite element analysis of intermediate crack debonding of fiber-reinforced polymer-plated reinforced concrete beams where multiple cracks may exist, an appropriate consideration of the interfacial damage during slip reversals is necessary in order to achieve accurate predictions on the behavior of fiber-reinforced polymer-to-concrete bonded interfaces, while for the steel bar-to-concrete interface, the consideration of the interfacial damage has insignificant effect on the numerical results if the yield strength and bar diameter are in their practical range.